Clinical factors affecting minor amputation in diabetic foot diseases at Tengku Ampuan Afzan Hospital, Kuantan - Zakaria@Mohamad, Zamzuri; Afifi, Mustaqim; Sharifudin, Mohd Ariff (Universiti Sains Malaysia, 2015)
Diabetic foot disease poses a substantial problem in Malaysian diabetic population. We evaluate the clinical factors affecting minor amputation in diabetic foot disease. A cross-sectional study enrolling patients admitted to orthopaedic wards of a single tertiary hospital for diabetic foot disease was conducted. Patients who had undergone major amputation or with medical condition above the ankle joint were not included. Clinical data were collected by measurement of ankle brachial systolic index and Semmes-Weinstein 5.07 gauge monofilament test with foot clinical evaluation using King’s classification respectively. The total number of patients included was 138, with mean age of 59.7 years (range 29 to 94 years old). Fifty patients (36.2%) had minor amputations. Poor compliance to diabetic treatment, King’s classification stage 5, low measures of ankle brachial systolic index, sensory neuropathy, high serum C-Reactive protein and high serum creatinine are significant predictive factors for minor amputation (P < 0.05). Identifying these risk factors may help in prevention of minor amputation and subsequently reduce limb loss in diabetic foot.